Studies On Laminar And Turbulent Reynolds Number For Standardized Nasal Cavity - Foo, Kar Yen (Universiti Sains Malaysia, 2017)
The airflow dynamics of a human nasal cavity is as important as its physiological functions, yet these dynamics are not well known. Numbers of features in nose have been argued to enhance airflow turbulence, thus increasing the heat exchange, humidifying inhaled air and greater exposure of moving air to nasal mucosa [1]. In conjunction to that, the flow regimes (laminar, transitional or turbulent) are studied in order to correlate the nasal morphology and turbulent airflow. Previous researchers mentioned that Reynolds number below 2000 is said to be laminar flow, while higher than that indicates turbulent flow. However, this is partially true because the flow is assumed to be in a straight, smooth-walled pipe. Hence, CFD simulation is carried out to further investigate the airflow patterns at varying flow rates. Laminar model is used to run the simulation for flow rates of 4.5 L/min, 7.5 L/min, 10 L/min and 15 L/min, while a two equation turbulence model, shear stress transport (SST) k-ω is adapted for flow rate of 18 L/min. Velocity magnitudes, velocity contours, velocity vectors and streamlines are collected for analysis. Besides that, experimental work using PIV is adapted as well in order to evaluate the flow characteristics in a model of human nasal cavity. The overall results suggested that airflow turbulence begin at flow rate of 18 L/min, where swirling and twisting flows are found at few regions. The aid of CFD and PIV allows better understanding and visualization of the airflow pattern in human nasal cavity.